Keefektifan Media Scrapbook Melalui Model Student Teams Achievement Division Terhadap Motivasi Dan Hasil Belajar IPS - Puspitasari, Nita; Purnamasari, Iin; Januar Saputra, Henry (Universitas Pendidikan Ganesha, 2018)
This study aims to determine the effectiveness of the Scrapbook Media through the Model of Student Teams Achievement Division on the Motivation and Learning Outcomes of Students in Class III of SDN Mranggen 2. The design of this study uses True Experimental Designs Pretest-Posttest Control Group Design. To analyze student learning motivation using test analysis data of observation motivation learning . The population in this study were all students of class IIIA and IIIB SD Negeri Mranggen 2. t can be concluded that there is effectiveness of scrapbook media through the Student Teams Achievement Division model on motivation and experimental class learning outcomes better than the control class. From the results of statistical analysis with t-test obtained obtained tcount = 2.869 and ttable = 2.086 with a significance level of 5% and N = 20, so that tcount > ttable (2,896 > 2,086) Ha1 is accepted. And the results of observations of learning motivation with t-test statistical analysis were obtained tcount = 3,787 and ttable = 2,086 with a significance level of 5% and N = 20, so that tcount > ttable (3,787 > 2,086) Ha2 is accepted. It can be concluded that scrapbook media through the Student Teams Achievement Division model is effective on student motivation and learning outcomes.